2015
DOI: 10.1093/mnras/stv731
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Plane of black hole activity in the optical band

Abstract: Black hole accretion and jet formation have long been thought to be scale invariant. One empirical relation suggesting scale invariance is the Fundamental Plane of Black Hole activity, which is a plane in the space given by black hole mass and the radio/X-ray luminosities. We search for an alternative version of this plane using the luminosity of [OIII] emission line instead of X-ray luminosity. We use a complete sample of 39 supermassive black holes selected from the Palomar Spectroscopic Survey with availabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 50 publications
(56 reference statements)
8
84
0
Order By: Relevance
“…This is in contrast with X-ray binaries and CVs, which generally show flaring at radio, optical, and X-ray wavelengths alongside strong Balmer emission lines. Similarly, the fundamental plane of black hole activity (e.g., Plotkin et al 2012;Saikia et al 2015) predicts L R significantly greater than~10 22 W Hz −1 when =Ĺ 1.5 10 X 44 erg s −1 .…”
Section: Disk-jet Connectionmentioning
confidence: 90%
“…This is in contrast with X-ray binaries and CVs, which generally show flaring at radio, optical, and X-ray wavelengths alongside strong Balmer emission lines. Similarly, the fundamental plane of black hole activity (e.g., Plotkin et al 2012;Saikia et al 2015) predicts L R significantly greater than~10 22 W Hz −1 when =Ĺ 1.5 10 X 44 erg s −1 .…”
Section: Disk-jet Connectionmentioning
confidence: 90%
“…The LLAGN sample used in the optical fundamental plane of black hole activity (Saikia et al 2015) is extracted from the Palomar Spectroscopic Survey (Ho et al 1995), comprising the nuclear region of 486 bright nearby galaxies with the B-magnitude in Tycho photometric band BT < 12.5 mag.…”
Section: Low Luminosity Agn In the Optical Fpmentioning
confidence: 99%
“…Moreover, a Kendall Tau Partial Correlation analysis was performed in Saikia et al (2015) with distance as the third variable, and the FP relation was found to be real even after taking into account the large range of inferred distance. The chi-square confidence map for the parameters of the fundamental plane was found to be an elongated ellipse, showing that the parameters are coupled (Saikia et al 2015). The uncertainties in the directly measured quantities like radio and [OIII] fluxes and the inferred quantities like distances and black hole masses are properly taken into account using the merit function while deriving the fundamental plane parameters.…”
Section: Low Luminosity Agn In the Optical Fpmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a hypothesis has been predicted by theoretical models (Heinz & Sunyaev 2003). Merloni et al (2003) as well as similar attempts to establish a relation connecting BH-powered jets of different M BH (Nagar et al 2002;Falcke et al 2004;Körding et al 2006;Plotkin et al 2012;Saikia et al 2015) have either explicitly avoided blazars focusing on low-luminosity active galactic nuclei (LLAGNs) or have included a handful of blazars. In the latter case, they have either ignored the relativistic effects or specifically chosen their sample to include only low-beamed sources.…”
Section: Introductionmentioning
confidence: 89%